Effects of high polyunsaturated fattyacid supplementation of diet on spatial memory and peroxisome proliferator activated receptor expression in rats - Hajjar, Toktam (2012)
The n-3 and n-6 polyunsaturated fatty acids (PUFAs) are essential dietary nutrients. The n-3 fatty acids are the most abundant fatty acid in the mammalian central nervous system and played important role in brain growth and function. DietaryPUFA have effects on membrane composition and regulation of gene expression. The PUFA-activated transcription factors regulate the genes involved in synaptic plasticity to improve memory formation. The aim of this research was to study the effects of diets supplemented with menhaden fish oil (source of n-3) and soybean oil (source of n-6) on the fatty acid profiles of the plasma and hippocampus, cognitive function developments, and expression of transcription factors associated with changes in morphological aspects of neurons in rats.In this study, forty male rats were randomly allotted into 4 groups of ten animals each namely CTRL (control) standard diet plus 7% butter (w/w), LMO (low menhaden fish oil) standard diet plus 0.23 % menhaden fish oil + 6.77 % soybean oil (w/w) with a n-6:n-3 ratio of 26:1, MMO (medium menhaden fish oil) standard diet plus 1 % menhaden fish oil + 6 % soybean oil (w/w) with a n-6:n-3 ratio of 22:1 and HMO (high menhaden fish oil) standard diet plus 3.5 % menhaden fish oil + 3.5 % soybean oil (w/w) with a n-6:n-3 ratio of 4.5:1. The fatty acid profiles of the diets, plasma and hippocampus of the rats were determined using standard extraction, methylation and gas-liquid chromatographic procedures. Results showed that docosahexaenoic acid (DHA)content and total n-3 PUFA in the plasma of the MMO and HMO groups were significantly higher and their n-6:n-3 ratio lower than CTRL group (P<0.05). HMO animals also had significantly higher DHA content, total n-3 PUFA, and less n-6:n-3 ratio in the hippocampus compared with CTRL group (P<0.05). The effects of above-mentioned changes in fatty acid composition on cognitive function were assessed for their spatial memory performance using the Morris Water Maze (MWM) test. The MWM test was performed in four phase namely spatial acquisition, probe trial, spatial reversal, and reversal probe trial. The results showed that the HMO and MMO rats had better spatial learning and re-learning compared with LMO and CTRL animals, indicating spatial memory abilities are related to the brain n-3 PUFAs status. The effect of increased brain n-3 fatty acids on hippocampus morphology was analyzed based on the changes in amount of presynaptic protein synaptophysin in hippocampus and the size of hippocampal neurons. Results indicated that the size of CA1 neurons was significantly increased in the HMO group compared to the CTRL group (P<0.05). Moreover, the expression of synaptophysin was increased in the rats supplemented with n-3 and n-6 fatty acids. The expressions of PPARα, PPARγ and c-Fos genes were assessed by real-time quantitative PCR method. Results showed that the dietary menhaden fish oil- and soybean oil supplementation upregulated PPARα and PPARγ genes expression (P <0.05) in the MMO and HMO groups compared to the CTRL group. However, the expression of c-Fos gene was not differentially expressed between animals fed the menhaden oil and soybean oil when compared with CTRL group. In conclusion, the dietary supplementation with higher level of n-3 fatty acids led to increased DHA and n-3 PUFAs content of the plasma and hippocampus, and PPARs upregulation. The increased n-3 PUFAs content in the hippocampus resulted in improved spatial memory in the rat, which may be also related to the alteration in synaptic protein and neuronal morphologic changes. The higher expression of PPARs suggests the association of these transcription factors in protein synthesis involved in the synaptic mechanisms that mediate the formation of spatial memory.